ANALISIS DAN OPTIMALISASI CAKUPAN AREA WI-FI DI KAMPUS UNIVERSITAS BINADARMA - Irwansyah Ibrahim; Fatoni Fatoni (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2022)
Abstract : One of the facilities for Lecturers, Educators and Students provided by the University of Bina Darma Palembang to access the internet is the WLAN network which is available on every floor of the Main Campus. Wireless Local Area Network (WLAN) is a computer network that uses radio and infrared frequencies as data transmission media. The existing problems Based on direct measurements on the 1st floor, 2nd floor, 3rd floor, 4th floor, 5th floor, 6th floor and 7th floor (attached), the signal strength on each floor is still categorized as unstable, namely poor (no signal). ) and fair (weak). The purpose of this study is to optimize the range of the Wi-Fi network signal using the Top-Down method. Top-Down method, is an approach that leads to the fulfillment of the company's business needs and goals. Through a clear business orientation, it can support the direction and goals of achieving company goals more efficiently and effectively.